Mathematics for physics e-module: Students’ interest in physics education based on gender - Darmaji Darmaji; Astalini Astalini; Dwi Agus Kurniawan; Riska Fitriani (Universitas Negeri Yogyakarta, 2022)
This study aimed to determine the differences in students’ interests in physics education at the University of Jambi towards using e-modules in physics-mathematics learning by observing the existence of gender differences. This study used a quantitative research method. The instrument used was student interest questionnaires. Furthermore, the data were analyzed using descriptive statistics and inferential statistics. The subjects of the study were 91 physics education students. The results of this study show that there are differences in students’ interests in the use of the physics-mathematical e-module in learning, namely the average student interest in the physics-mathematical e-module which female students best own, namely in class A with an average of 37.94, slightly higher than the average interest of male in class C, which is 35, 20. Differences in interests are caused by internal factors of these students, namely diligent and consistent behavior in learning. Female students are more diligent in studying than male students, so female students have a higher interest in learning than males